2019
DOI: 10.1021/acs.jpcb.9b05375
|View full text |Cite
|
Sign up to set email alerts
|

High Polymer Mass Densities at the Mouths of Carbon Nanotubes (CNTs) Control the Diffusion of Small Molecules through CNT-Based Polymer Nanocomposite Membranes

Abstract: Detailed molecular dynamics (MD) simulations of model single-walled carbon nanotube (CNT) membranes based on atactic poly­(methyl methacrylate) (aPMMA) indicate that PMMA chains significantly penetrate nanotubes through their faces. They predict very high-density values of the polymer in the interfacial area around the CNT mouths that can exceed by 50% the density of the bulk polymer at the same thermodynamic conditions. This dramatically decreases the diffusivity of relatively small penetrants (in our study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Our purpose in the present study is to carry out a systematic analysis of the cavities of free volume accessible to a small penetrant molecule in a polymer nanocomposite containing CNTs, of their clusters, and of the connectivity of these clusters. Our work is motivated by the findings of the recent MD study already mentioned above (ref ), which indicated significant penetration of PMMA chains inside CNTs in model CNT-PMMA nanocomposites. It involves a geometric analysis of free volume in these model CNT-polymer configurations, which allows one to determine the holes accessible to water molecules and identify their clustering as well as the network of pathways through which a water molecule can diffuse from one such cavity to another, inside the nanocomposite.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Our purpose in the present study is to carry out a systematic analysis of the cavities of free volume accessible to a small penetrant molecule in a polymer nanocomposite containing CNTs, of their clusters, and of the connectivity of these clusters. Our work is motivated by the findings of the recent MD study already mentioned above (ref ), which indicated significant penetration of PMMA chains inside CNTs in model CNT-PMMA nanocomposites. It involves a geometric analysis of free volume in these model CNT-polymer configurations, which allows one to determine the holes accessible to water molecules and identify their clustering as well as the network of pathways through which a water molecule can diffuse from one such cavity to another, inside the nanocomposite.…”
Section: Introductionmentioning
confidence: 84%
“…The model CNT-PMMA nanocomposite structures analyzed have already been described and characterized in two previous contributions. , They comprise a pure atactic poly­(methyl methacrylate) matrix (system 1) and four single-walled carbon nanotube-based nanocomposites (systems 2–5). System 1 consists of 280 45 monomer units long (molecular weight 4500 g/mol) PMMA chains in an orthorhombic cell subject to periodic boundary conditions and edge lengths approximately equal to 125 Å.…”
Section: Methodology and Systems Studiedmentioning
confidence: 99%
See 3 more Smart Citations